SUSTAINABILITY ANALYSIS OF EXTERNAL OVERSIGHT OF REGIONAL PUBLIC SERVICES FROM THE PERSPECTIVES OF REGULATION, INSTITUTIONAL FRAMEWORK, FUNDING, IMPLEMENTATION, AND TERRITORIAL ASPECTS - Andi Setyo Pambudi; Rahmat Hidayat; Istiqlal Abadiyah Sukma Putri; Muhammad Reffo Bhawono Yudho (Post Graduate School of Government Science, 2025)
External oversight of public services in the regions aims to ensure that services operate optimally, effectively, efficiently, transparently, and accountably. This oversight is crucial for maintaining service quality, preventing abuse of authority, and improving public satisfaction. The Ombudsman of the Republic of Indonesia is mandated by regulation to carry out this oversight, as outlined in Presidential Regulation Number 18 of 2020 on the 2020-2024 National Medium-Term Development Plan (RPJMN). This study examines the Ombudsman's role in supporting national development planning, evaluates the resolution of public complaints, assesses compliance with public service standards, and explores evidence-based oversight in the regions. A qualitative descriptive approach incorporates literature studies, target and realization data analysis, and focus group discussions (FGD). The findings reveal significant challenges the Ombudsman faces, including regulatory, institutional, funding, operational, and geographical limitations. These constraints hinder target achievement, particularly at the regional representative level, where oversight is often limited to sample-based activities. The study highlights the need for policymakers to prioritize public service oversight system improvements. Strengthening the Ombudsman's resources and authority is essential for fostering a more professional, fair, equitable, and high-quality public service system, supporting and accelerating national public service reform.